Application of Technology in the Learning Process of Elementary School Teachers at SD Inpres Malakantu - Istifarah; Syamsuddin; Sulaeman Miru; Kadek Agus Dwiwijaya (PT. Global World Scientific, 2024)
This study aims to enhance the quality of teaching in elementary schools by leveraging technology, with a focus on developing students' digital literacy skills. A descriptive qualitative method was used with two teachers as research subjects at SD Inpres Malakantu. The study's results showed a lack of technology use in learning, with the primary teaching materials still being books. The researcher provided examples of multimedia-based learning materials, particularly utilizing the slide master feature in Microsoft PowerPoint, Canva, and Google Classroom. This study found that the limitations of teachers' technical skills can be overcome through the development of skills using technology. The integration of technology in elementary schools is considered to increase student engagement and the quality of learning. The use of technology at SD Inpres Malakantu was identified as a solution to challenges in delivering learning materials. Research recommendations include strengthening teacher technology skills training, full support from schools and the government in integrating technology into the curriculum, and further research to understand the long-term impact of technology implementation on student achievement and their learning experiences.